« Et tout, le monde, déteste la métropole ? » Entretien avec la critique sociale - Matthieu Adam (Métropoles, 2021)
On banners and graffitis or in the writings of political activists, the “metropolis” seems to have become a keyword for contemporary urban social movements in France. Beyond the slogans, what does the term refer to? How does it enable one to theorise, and above all, to mobilise and act? This collective interview with authors who address the topic in three recent books of social critique (Contre Euralille: une critique de l’utopie métropolitaine, Le Désert Urbain, and Quartiers vivants) questions the term's theoretical and practical potential. Instead of adopting an external and overbearing stance that seeks to objectify political positions, this text seeks to contribute to the existence of a debate on how to think and foster urban social movements.